The Oral health knowledge and behavior of clinical medical and dental students in a Northeastern Nigerian University - Janada, Yusuf; Ikhodaro, Idon Paul; Ibiyemi, Olushola (International Association for Dental Research (Nigeria Division), 2019)
Abstract Objective: Medical and dental students as future health care professionals should be aware of oral health maintenance. Therefore, this study aimed to determine their oral health knowledge and behavior in a Northeastern Nigerian University. Materials and methods: One hundred and fifty clinical medical and dental students were interviewed on their age, gender, course of study, level of study, knowledge of oral health care, oral health practices and psychosocial impact of oral health using an interviewer-administered questionnaire. After completing the questionnaire, the students were examined for dental caries and oral hygiene status. The student t-test was used to compare means while the chi-square test was used to test associations between categorical variables at p<0.05. Results: The mean (SD) age of students was 24.5 (2.70) years, males constituted 61.3%. One hundred and twenty-six (84.0%) students had good knowledge of oral health care, 97.7% and 78.5% of dental students and medical students having good knowledge respectively (p=0.003). There was no statistical significant association between socio-demographic characteristics and oral health practices of the students (p>0.05).  Only age group was statistically significantly associated with psychosocial impact (p<0.05). Forty-five (30.0%) and 74 (49.3%) students had dental caries, and poor oral hygiene respectively. Conclusions: There was a high level of good knowledge of oral health care among these Nigerian Medical and Dental students. Dental students had better knowledge of oral health care than medical students. Younger age group of students reported higher psychosocial impact of oral health care on daily activities than older ones.